X-ray μ-CT data reconstruction, image stacks of selected samples from IODP Site 385-U1547 - Wolf-Achim Kahl; Christophe Galerne (PANGAEA, 2025)
This contribution comprises true-3D volume datasets (Digital drill cores), acquired by a X-ray Computed Microtomography (μ-CT) survey on selected drill core material recovered from Site U1547, Holes B, D, and E, drilled by IODP Expedition 385 in the Guaymas Basin, Gulf of California (for more details see Teske et al., 2021a). The six samples reported are igneous material from a single igneous funnel-shaped sill intrusion. The samples were scanned as quarter cores and selected along the sill thickness (at least 100 m thick) and across the sill radius (Holes are distributed along a profile cutting through the sill center in a map view) to enable visualization of the main textural variations along a cross-section of the sill (see Galerne et al. (in Rev)). Note that a same sample has been measured twice at distinct resolution in order to provide a sensitivity analysis of the porosity. This analysis is completed by a distinct measurement technic called moisture and density (i.e. MAD, see Teske et al., 2021b) and discuss in Galerne et al., (in review). The X-ray μ-CT scans were performed using the ZEISS Xradia 520 Versa system of the MAPEX Center for Materials and Processes at the University of Bremen, Germany. This μ-CT survey has been conducted as part of IODP Expedition 385 Post-cruise research led and secured by Christophe Galerne (German Research Foundation (DFG) funding priority program SPP 527. Project number 447431016). The samples were quarter cores or irregularly shaped pieces. The reconstructed image material has resolutions between 8.83 and 35.4 μm/voxel (depending on the sample size and geometry). The μ-CT-derived image volumes comprise the true 3-D spatial arrangement of fabric compounds in the rock. In the reconstructed 16-bit greyscale volume data, areas of highly attenuating phases (e.g. sulfides, calcite) are encoded in light grey values, whereas areas of low X-ray absorption are color-coded in dark grey (e.g. clays) or black (e.g. voids, cracks). In order to facilitate straightforward access to the digital drill core image material, the volume data is provided as a zipped stack of tif images. In addition, each digital drill core is characterized by three types of visualization: (i) shaded and classical texture-based volume rendering (volren), (ii) maximum intensity projection (volren-MIP): visualization of the highest intensity in a data volume along the current line of sight, and (iii) three perpendicular virtual cutting planes (3-slices). As an added value to the non-destructive visualization procedure, the reconstructed X-ray micro-CT scans of the studied drill core material provide volume reconstructions which can serve as digitypes that may be studied as digital facsimile without the necessity of consulting / modifying / destructive interactions of the actual type specimens (e. g. for investigations regarding the fabric relations). These image data can be used for quantitative 3D image analysis, e. g. to derive empirical relations between porosity, the extent of replacement of primary phases, and the distribution of secondary phases (and many more).